MORPHOMETRIC DESCRIPTION AND BEHAVIOURAL ECOLOGY OF Analeptes trifasciata FABRICIUS 1775 (COLEOPTERA: CERAMBYCIDAE) ON CASHEW (Anacardium occidentale LINNAEUS 1753) IN NIGERIA (2011)
The infestation of cashew by Analeptes trifasciata is on the increase and this poses serious threat to cashew cultivation in Nigeria. Base-line information on the distribution and behavioural ecology of A. trifasciata in Nigeria is needed for its control. This study was conducted to provide more information on the morphology, distribution and behavioural ecology of A. trifasciata in Nigeria. A survey of the geographical spread of A. trifasciata infestation was conducted in 25 cashew growing states by random sampling of 1000 trees/state from 2005 to 2006. The morphormetric and behavioural studies were carried out from 2006 to 2007. The morphometric characteristics of A. trifasciata were taken with a venier caliper. Monthly infestation rates of cashew trees were studied in two states (Oyo and Kogi), with high infestations. Cashew trees (300) were randomly sampled in each state to determine the number of A. trifasciata and girdled-tree-branches hanging or on the ground. The preferred height of girdling by A. trifasciata was determined by measuring infested trees with a calibrated pole, while preferred diameter of girdled-branches was determined by measuring the base of randomly collected branches. Feeding preference was investigated using stems of cashew and seven alternate host plants. These plants were placed in a feeding preference chamber at equidistance of 30 cm before the introduction of 80 pairs of males and females A. trifasciata. Data were analyzed with Student’s t-test at p < 0.05. Analeptes trifasciata was found in South-East, South-West and North-Central geopolitical zones. Pronounced infestation levels of 42.7% to 82.6% were recorded, the highest in Kogi State (82.6%) followed by Oyo State (79.3%). Adult A. trifasciata are large beetles, 4.0 ± 0.1 cm long. The fresh body weights of the females (3.0 ± 0.1 g) were more than those of the males (2.7 ± 0.1 g). The males possessed significantly longer antennae (6.0 ± 0.1 cm) than the females (5.3± 0.0 cm). Peak infestation (117 - 130 Analeptes) was recorded in September to December 2007, and least (7 Analeptes) in June. Analeptes trifasciata population was more abundant in Oyo State (554.3 ± 41.3) than Kogi State (360.7 ± 42.4). Girdled-stems hanging on tree canopies in Oyo State (546.7 ± 32.4) significantly differed from those on the ground (425.3 ± 18.2). A higher number of girdled-branches, 535.8 ± 27.6/hectare were recorded for Kogi State when ii compared with 323.7 ± 18.4 for Oyo State. The beetles showed girdling preferences for moderately tall trees (2.0 to 5.0 m) and medium sized branches (4.0 to 6.0 cm diameter). The beetles consistently fed more on cashew stems in the chamber, while Spondias mombin and Lannea welwitschil were the preferred alternate host plants. The wide spread infestation of cashew trees in most states has made Analeptes trifasciata a pest of economic importance. Their large size was an adaptation for enhanced girdling, which led to significant damages in highly infested plantations. Control measures in Nigeria should target the peak periods of infestation to reduce losses in cashew production.